Strategies for Recognition of Stem-loop RNA Structures by Synthetic Ligands: Application to the HIV-1 Frameshift Stimulatory Sequence - Palde, Prakash B. (2010)
Production of the Gag-Pol polyprotein in human immunodeficiency virus (HIV) requires a -1 ribosomal frameshift, which is directed by a highly conserved RNA stemloop. Building on our discovery of a set of disulfide-containing peptides that bind this RNA, we describe medicinal chemistry efforts designed to begin to understand the structure-activity relationships and RNA sequence-selectivity relationships associated with these compounds. Additionally, we have prepared analogues incorporating an olefin or saturated hydrocarbon bioisostere of the disulfide moiety, as a first step towards enhancing biostability. The olefin-containing compounds exhibit affinity comparable to the lead disulfide, and importantly have no discernable toxicity when incubated with human fibroblasts at concentrations up to 1 millimolar.